A simplified method for determining acceleration amplitude of prestressed concrete floor under individual jumping load. (12th March 2018) - Liu, Jiepeng; Cao, Liang; Zhou, Zikai
Summary: Modern long‐span prestressed concrete (PC) floors typically possess low damping and low natural frequency, presenting a potential vibration sensitivity problem induced by human activities. Field test and numerical analysis methods are available to study this kind of problems but would be inconvenient for design engineers. This paper proposes a simplified method to determine the acceleration amplitude of a PC floor subjected to individual jumping load, carrying out through a mix of analytical and experimental techniques. To theoretically analyze the acceleration response, the PC floor was simplified as an anisotropic rectangular plate and the mode decomposition method was used. To facilitate the calculation of the acceleration amplitude a P, a frequency‐dependent coefficient β J is introduced, which depends on the geometry and support condition of the PC floor and dynamic amplification factor K J . Field tests on 7 PC floors with various boundary conditions and fundamental natural frequencies were conducted to determine β J coefficient. Based on the test results, practical formulas for β J coefficient is first proposed, followed by that for acceleration amplitude a P . The proposed simplified method is easy for practical use and will yield safe and conservative structural designs.